Seismic performance of metallic braced frames by pushover analyses - Braz-César, Manuel (2009)
A preliminary investigation is presented on a pushover analysis used for the seismic performance of metallic braced frames equipped with diagonal X-bracing and K-bracing systems. Three steel frames were analysed corresponding to 3, 6 and 10 floor regular buildings. The frames were modelled in the MIDAS/Civil finite element software and in the analyses nonlinear static methods were used to obtain the pushover curve. The principal objective of this article is to compare the evaluation of the structural performances of these buildings with respect to the proposed N2-method, and so also of the consequent convenience of using pushover methodology for the seismic analysis of structures.